2019
DOI: 10.1002/cbdv.201900004
|View full text |Cite
|
Sign up to set email alerts
|

Daturanolide A–C, Three New Withanolides from Datura metel L. and Their Cytotoxic Activities

Abstract: Three new withanolides (1–3), named as daturanolide A–C, along with six known withanolides (4–9) were isolated from the flowers of Datura metel L. Their structures with absolute configurations were elucidated by a series of spectroscopic methods, electronic circular dichroism (ECD) analyses, and X‐ray crystallography. All the isolates were evaluated for cytotoxicity against five human cancer cell lines (HCT116, U87‐MG, NCI‐H460, BGC823, and HepG2), and 6 exhibited marked cytotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The non-glycosidic compound of the plant exhibited a significant antiproliferative effect on the HCT-116 cell line (IC 50 : 3.2 ± 0.2 µM) ( Monira and Munan, 2012 ). In another study, daturanolides A–C, along with 6 previously described withanolides (4–9), were found in the flowers of D. metel ( Wang et al, 2019 ), as shown in Fig. 6 .…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…The non-glycosidic compound of the plant exhibited a significant antiproliferative effect on the HCT-116 cell line (IC 50 : 3.2 ± 0.2 µM) ( Monira and Munan, 2012 ). In another study, daturanolides A–C, along with 6 previously described withanolides (4–9), were found in the flowers of D. metel ( Wang et al, 2019 ), as shown in Fig. 6 .…”
Section: Resultssupporting
confidence: 55%
“…Different glycosidases are effectively inhibited by nitrogen-rich polyhydroxylated compounds. They can be utilized for treating many diseases, including cancer, diabetes, immunological diseases, and virus-causing infections ( Wang et al, 2019 ). Including Datura, other 14 Solanaceae family plants contain a significant number of withanolides, and these compounds have a notable anti-cancer effect by creating oxidative stress and downregulating NF-kB, transcription factor STAT3, and Hsp90.…”
Section: Resultsmentioning
confidence: 99%
“…Daturanolides 61 – 63 ( Figure 9 ), isolated from the flowers of D. metel L, were also evaluated for their cytotoxicity against five human cancer cell lines (HCT116, U87-MG, NCI-H460, BGC823, and HepG2) [ 84 ]. However, none of the compounds showed significant activities against the tested cell lines.…”
Section: Withanolides As Anti-cancer Agentsmentioning
confidence: 99%